An Analysis of Flouting Maxim Used by Mowgli in The Jungle Book Movie: Pragmatics Study - Lestari, Muhsinah Dwi; Prasetyani, Nuning Yudhi; Qaniah, Binti (General English Education, 2025)
This study aims to identify and describe the functions of flouting maxims in The Jungle Book movie using a pragmatic approach. Employing a descriptive qualitative method, the research analyzes Mowgli's utterances to reveal four types of flouting maxims: quantity, quality, manner, and relation. The most frequently flouted maxim is relation, highlighting Mowgli's strategies to survive and stay safe in the forest. Conversely, Mowgli rarely flouts the maxim of quality due to his sense of gratitude toward those who saved him. The research also identifies three functions of flouting maxims: competitive, collaborative, and convivial. Among these, the collaborative function is the most common, as Mowgli often seeks cooperation with various animals. In contrast, the convivial function is rarely used, reflecting his effort to maintain politeness and avoid causing offense. This study provides a concrete example of the application of pragmatic theory, particularly the cooperative principle, demonstrating its relevance in understanding characters' communication strategies in films.